2012
DOI: 10.4161/cbt.20079
|View full text |Cite
|
Sign up to set email alerts
|

TRPM8 ion channel is aberrantly expressed and required for preventing replicative senescence in pancreatic adenocarcinoma

Abstract: Pancreatic adenocarcinoma is mostly fatal and generally resistant to conventional treatments, such that effective therapies with tolerable side effects are desperately needed. Ion channels including the transient receptor potential (TRP) channels have been implicated in human malignancies, but their roles in pancreatic cancer were mostly unknown. Recent identification of the melastatin-subfamily members of the TRP family of ion channels, and their functions in pancreatic epithelia and adenocarcinoma, is expect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 34 publications
1
56
1
Order By: Relevance
“…Therefore, TRPC6 could potentially be of importance in the progression of IVD degeneration linked to cell senescence, but further studies are needed. In fact, the role of TRP channels in modulating senescence is also known for other cell types, such as endothelial cells (TRPC5) [47], pancreatic adenocarcinoma cells (TRPM7, TRPM8) [48,49] and lung fibroblasts (TRPC6) [30].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, TRPC6 could potentially be of importance in the progression of IVD degeneration linked to cell senescence, but further studies are needed. In fact, the role of TRP channels in modulating senescence is also known for other cell types, such as endothelial cells (TRPC5) [47], pancreatic adenocarcinoma cells (TRPM7, TRPM8) [48,49] and lung fibroblasts (TRPC6) [30].…”
Section: Discussionmentioning
confidence: 99%
“…On a more positive note, in a second independent study, the combination of anti-TRPM7 siRNA and gemcitabine produced enhanced tumor cell killing compared with gemcitabine alone (Yee et al, 2012b). A subset of patients with pancreatic carcinoma aberrantly expresses TRPM8 (Yee et al, 2012a). Targeted inhibition of TRPM8 in these patients may increase survival.…”
Section: G Transient Receptor Potential Channels In Cancermentioning
confidence: 99%
“…In pancreatic ductal adenocarcinoma, TRPM7 (Rybarczyk et al, 2012) and TRPM8 (Yee et al, 2012a) have been identified as potential therapeutic targets. Compared with non-neoplastic pancreatic tissue, TRPM7 is highly expressed (13-fold) in pancreatic cancer.…”
Section: G Transient Receptor Potential Channels In Cancermentioning
confidence: 99%
“…Small interfering RNA-mediated silencing of TRPM7 or TRPM8 reduces cellular proliferation, impairs cell cycle progression, and induces replicative senescence in the pancreatic cancer cells. 34,[45][46][47][48] These data further demonstrate the potential of human orthologs to developmental regulators of exocrine pancreas in zebrafish as clinical biomarkers and therapeutic targets in human pancreatic cancer. 47 …”
Section: Translating Zebrafish Into Human Pancreatic Cancermentioning
confidence: 88%
“…7A, B). Based on these study results, we discovered that TRPM7 and its subfamily member TRPM8 are aberrantly over-expressed in human pancreatic adenocarcinoma 34,[45][46][47] ( Fig. 7C, D).…”
Section: Translating Zebrafish Into Human Pancreatic Cancermentioning
confidence: 99%